Combating homophobia : preliminary results of a school-based program to reduce discrimination against same-sex attracted youth - Higgins, Daryl (WAS 2001 : PariSEXO 2001 : XVth World Congress of Sexology, 2001)
Two key determinants of mental health are (a) freedom from discrimination and (b) social connectedness. Same-sex attracted youth who are subjected to violence and discrimination, or who experience homophobia in their everyday lives are at greater risk of mental health problems, including suicidal thoughts and behaviours. As one of the most significant sites of homophobia is the school, a 6-week school-based program designed to help students explore their attitudes to gays and lesbians was developed, called “Pride & Prejudice”. In order to evaluate the usefulness of the program, students’ attitudes were measured before and after their participation. Variables assessed were: beliefs about gender roles, social desirability, attitudes to gay men and lesbians, social connectedness, self-esteem, and attitudes to race. Attitudes towards gay men held by students were significantly more positive after the program, and the level of attendance during the program significantly predicted > this change. A significant positive change also occurred in attitudes towards lesbians. Process evaluation showed that students generally viewed the program positively. From this preliminary data, it can be concluded that school-based programs delivered to individual classes in which students are given the opportunity to explore their attitudes towards lesbians and gay men are likely to lead to a significant reduction in homophobia. Health-promoting schools now have available to them an effective tool for promoting opportunities for students to reflect on their attitudes towards gay men and lesbians, and other aspects of “social diversity”. It is hoped that school-wide implementation of such a program will eventually lead to a reduction in the discrimination same-sex attracted youth often experience (either directly, or indirectly), and improve the social-connectedness of all students.